Head trauma: A significant public health concern among young men in Botswana. Etiology referral patterns and opportunities for interventions - Megan Cox; Timothy Becker; Mpapho Motsumi (AOSIS, 2018)
This study aims to present and discuss acute Head Injury (HI) presentations including etiology, referral patterns and disposition in patients presenting to a major referral hospital in Gaborone, Botswana. Cross-sectional, retrospective data collection from July 2015 through September 2015 extracted descriptions of patient demographics, mechanism of injury, comorbidities, diagnosis and disposition from Emergency Centre (EC) records. 360 HI patients presented in three months, averaging four per day and increasing on weekends and end of the month. HI disproportionately impacted young adult males, with motor vehicle accidents accounting for 38%, violence implicated in 39% and 80% recorded as blunt trauma. HIV status was unknown for 84% of patients at the time of presentation and 10% of patients were recorded as HIV positive. Patients referred from external hospitals had a higher admission rate. HI in young males is a significant trauma burden in this hospital, similar to the known regional trauma patterns. More studies regarding trauma, alcohol, and violence related to paydays should be considered to investigate and reduce the burden of HI in Botswana.